Am I losing it? - Norman M. Mann (Greater Baltimore Medical Center, 2012)
Complaints of memory loss are frequent as one ages. Individuals worry about the presence of Alzheimer's disease, but the presence of other intact intellectual abilities is reassuring to these people. We do not know the cause of Alzheimer's disease. There are now 5.4 million confirmed cases in the United States. We know that the disease is an age-related, non-reversible brain disorder that develops over many years. Investigation is helped with the use of structural imaging (magnetic resonance imaging or computed tomography). Functional imaging is also valuable. Therapy for the problem involves various drugs; these help but do not cure the difficulty.